Revalidation and redescription of Brachymystax tsinlingensis Li, 1966 (Salmoniformes: Salmonidae) from China - Xing, Ying-Chun; Lv, Bin-Bin; Ye, En-Qi; Fan, En-Yuan; Li, Shi-Yang; Wang, Li-Xin; Zhang, Chun-Guang; Zhao, Ya-Hui (Zootaxa, 2015)
Brachymystax tsinlingensis Li, 1966 is revalidated and redescribed. It can be distinguished from all congeners by the following combination of characteristics: no spots on operculum; gill rakers 15-20; lateral-line scales 98-116; pyloric caeca 60-71. Unique morphological characters and genetic divergence of this species are discussed. This species has a limited distribution in several streams of the middle part of the Qinling Mountains in China. Methods for management and protection of B. tsinlingensis need to be re-evaluated.